3D quantitative analyses of angiogenic sprout growth dynamics. Issue 5 (25th March 2013) - Shirinifard, Abbas; McCollum, Catherine W.; Bolin, Maria Bondesson; Gustafsson, Jan‐Åke; Glazier, James A.; Clendenon, Sherry G.
<x xml:space="preserve">Abstract</x> Background: Zebrafish intersegmental vessel (ISV) growth is widely used to study angiogenesis and to screen drugs and toxins that perturb angiogenesis. Most current ISV growth assays observe the presence or absence of ISVs or perturbation of ISV morphology but do not measure growth dynamics. We have developed a four‐dimensional (4D, space plus time) quantitative analysis of angiogenic sprout growth dynamics for characterization of both normal and perturbed growth. Results: We tracked the positions of the ISV base and tip for each ISV sprout in 4D. Despite immobilization, zebrafish embryos translocated globally and non‐uniformly during development. We used displacement of the ISV base and the angle between the ISV and the dorsal aorta to correct for displacement and rotation during development. From corrected tip cell coordinates, we computed average ISV trajectories. We fitted a quadratic curve to the average ISV trajectories to produce a canonical ISV trajectory for each experimental group, arsenic treated and untreated. From the canonical ISV trajectories, we computed curvature, average directed migration speed and directionality. Canonical trajectories from treated (arsenic exposed) and untreated groups differed in curvature, average directed migration speed and angle between the ISV and dorsal aorta. Conclusions: 4D analysis of angiogenic sprout growth dynamics: (1) Allows quantitative assessment of ISV growth dynamics and perturbation, and (2) provides critical inputs for computational models of angiogenesis. Developmental Dynamics 242:508–516, 2013. © 2013 Wiley Periodicals, Inc.